EFEKTIFITAS PENGGUNAAN PORTAL AKADEMIK DI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS SAM RATULANGI MANADO - MOTULO, BRENDA NATALIA; Ogotan, Martha; Londa, Very (Sam Ratulangi University, 2016)
ABTRACK : This study aims to determine the effectiveness of using the Academic Portal at SamRatulangi University, especially the Faculty of Social and Political Sciences. This research was conductedusing qualitative descriptive method. The results showed that: Use of Academic Portal Fispol Sam RatulangiUniversity in Manado was very helpful during the process of learning but not fully effective. Entry portalprovides benefits to the academic institutions, students, lecturers and managers to be able to present all theneeds, such as: Card Planing Study, Lecture Attendance List, Card Study Results, academic transcripts, aswell as matters relating to the management of Graduation and diploma and other data needs. Use ofAcademic Portal in Fispol Unsrat not been effective in terms of time and costs and yet provide satisfaction forall users; Factors Supporting Use of Academic Portal Fispol Sam Ratulangi University in Manado are allelements of the campus, namely: leadership, staff and students as well as quality assurance. In addition, thecentral and provincial government support and human resources employees very major contribution inacademic portal usage; The obstacles encountered in the use of Academic Portal Fispol Sam RatulangiUniversity in Manado is internal constraints and external constraints. Internal constraints are constraintsthat come from the users in this case are the students and lecturers as well as the manager himself who oftenlack discipline in terms of time to access the portal, causing entered data can not be registered because itdelays access and input data online. External constraints are the constraints that come from outside which inthis case is a disorder of the Internet network; and efforts are being made to overcome the obstaclesencountered in the use of the portal academic Fispol Sam Ratulangi University in Manado not all beimplemented must be through socialization and introduction to the faculty and students back, also in theform of an announcement on the bulletin boards of faculty regarding the charging time and the deadline forfilling the portal academic , but it also attempted dissemination through seminars to introduce more featuresand for the smooth process of the lecture. Besides maximizing the existing infrastructure to support theoperation of the academic portal usage such as efforts to overcome problems with the procurement networkof free internet network in a campus environment and other measures which have not been done.Keywords: Effectiveness, Academic Portal